As Mudanças Organizacionais e seus Gestores nas Empresas na Era da Informação - Mattos, Lissandra Kerppers (2002)
In the past, the changes made in organizations were from decisions made by senior administrators and were implemented through authority and power. This sort of change doesn¿t work today because at a time when knowledge is one of the main tools for development, senior administrators need the participation of employees who directly handle strategic information for the company, having the necessary data for the conception, planning and execution of changes. Companies have begun to realize that the use of their own competent staff is the way to implement faster and more efficient strategic maneuvers. Which means, for a successful change, the whole process has to involve their employees. They have to develop efficient methods, such as, techniques for analysis, problem solution, team work, system modeling, change in attitudes and behavior, and management of the organizations culture. These methods define the professional profile of those responsible for the change. Today, each administrator must have the necessary qualifications, knowledge, and competence to identify the need for an organizational change and its introduction. In truth, each administrator is responsible for the structural change in his area and the standardization of his services.